REQUESTING IN ENGLISH AS A LINGUA FRANCA: PROFICIENCY EFFECTS IN STAY ABROAD - Vilar Beltrán, Elina (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This article reports on an empirical study designed to assess pragmatic awareness and production of 104 nonnative speakers of English of two different proficiency levels (intermediate and advanced). The paper first frames the study providing information on the users of English as a Lingua Franca (ELF), a new communicative competence model that takes into account lingua franca users, and studies dealing with ELF topics. This is followed by the description of the methodology employed and a discussion of the results. The findings confirm that proficiency level has effects on the awareness and production of appropriate and correct request acts and request act modifiers. Statistical analyses show that advanced learners produce more appropriate and accurate requests than intermediate participants, which was also the case for most internal request modifiers. Advanced learners also appear to be better at assessing pragmatic and grammatical failure of some types of request strategies. Resumen En este artículo se describe un estudio empírico diseñado para evaluar la conciencia y la producción pragmática de 104 hablantes no nativos de inglés con dos niveles de competencia lingüística diferentes (intermedio y avanzado). En primer lugar se presenta el contexto, se introduce brevemente un nuevo modelo de competencia comunicativa basado en usuarios de inglés como lengua franca y se señalan algunos de los estudios más relevantes. A continuación se describen la metodología empleada y los resultados. Estos confirman que el nivel de competencia tiene efectos sobre la conciencia y la producción pragmática de peticiones apropiadas y gramaticalmente correctas y también de sus elementos mitigadores. Los análisis estadísticos muestran que los estudiantes de nivel avanzado producen peticiones más apropiadas y correctas que los participantes intermedios, y lo mismo ocurre con los elementos de mitigación. También parecen mostrar que los estudiantes de nivel avanzado evalúan mejor los fallos pragmáticos y gramaticales de algunos tipos de peticiones.